MOTIVATION AND SATISFACTION OF HEALTHCARE WORKERS INVOLVED IN SURFACE CLEANING AND DISINFECTION - Rigonato, Elaine Mazuqui; Santos Junior, Aires Garcia dos; Lima, Helder de Pádua; Oliveira, Jones Sidnei Barbosa de; Angeloni, Natália Liberato Norberto; Gonçalves, Viviane Perbeline; Silva, Maria Heloísa do Nascimento (Cogitare Enfermagem, 2024)
Objective: To verify the levels of motivation and satisfaction of workers responsible for cleaning and disinfecting surfaces. Method: This was a cross-sectional, quantitative study of 69 healthcare workers at a Severe Acute Respiratory Syndrome Treatment Unit in Mato Grosso do Sul, Brazil. Data was collected between April and May 2022, using a sociodemographic and professional questionnaire and Motivation and Job Satisfaction Scales. Categorical variables are represented by absolute and relative frequencies, numerical by mean, standard deviation, median, and interquartile range. Results: The variables 'Because I like this job' (5.5), 'Because this job fits in with my personal values' (5.16), and 'Because my job is my life, and I don't want to fail' (4.25) showed the highest mean scores for motivation. There was agreement on job satisfaction (4.07) and not wanting another job (2.6). Conclusion: Knowledge about everyday organizational life in health services has increased, enabling actions to be planned that have an impact on working conditions.